Performance analysis of Newton-Raphson Power flow computations based on Power and Current Mismatches - Lukmanul Hakim; Khairudin Khairudin; Zulmiftah Huda (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
This work studies the performance of single-phase power flow computations implemented using vector-based Python scripting language. Two approaches are considered, namely the current mismatch and power mismatch based on Newton-Raphson method. Both approaches are developed using rectangular coordinates and tested through a variety of IEEE test systems modelling high voltage transmission networks. The computational burden and accuracy of both implementations are duly discussed. This work will be later incorporated into our vector-based Non-linear Primal-Dual Interior Point Method as constraints.